Team zhongyong thinking and team incremental and radical creativity - Yi Lang; Fan Zhang; Jun Yin (Journal of Innovation & Knowledge, 2022)
Zhongyong thinking is a cognitive thinking style that plays a pivotal role for Chinese employees and organizations, and whether it harms or benefits creativity has long been discussed. In this study, we empirically examine the relationship between team Zhongyong thinking and team incremental and radical creativity. Specifically, we propose that team Zhongyong thinking has a stronger indirect relationship with team incremental creativity than with radical creativity via team decision comprehensiveness. Furthermore, environmental dynamism moderates this indirect relationship, and team Zhongyong thinking has a stronger indirect effect on team creativity via team decision comprehensiveness when environmental dynamism is higher. Data collected from 106 teams comprising 770 subordinates and 106 supervisors in China using the survey method reveal that team Zhongyong thinking is positively related to team incremental creativity but not team radical creativity via team decision comprehensiveness. Moreover, environmental dynamism moderates the influence of team Zhongyong thinking on team incremental creativity via team decision comprehensiveness. Specifically, when environmental dynamism is higher, this influence is stronger. These findings imply that via extensive information searching and inclusive decision-making, team Zhongyong thinking can benefit team incremental creativity, especially in a changing environment, but this thinking style has no significant influence on team radical creativity.